Reversing the Influence: How Teacher Technology Adoption Shapes Principal Digital Leadership Practice? - Rui Zhu; Bity Salwana Alias; Mohd Izham Mohd Hamzah (International Journal of Educational Development, 2025)
In the field of leadership, traditional literature has largely focused on how followers are influenced by leaders or how they act as mediators between leadership and behaviors. However, leadership is a process of interaction, leadership research should shift this focus to emphasize the influence of followers on leaders. Therefore, this research examines how teacher technology adoption impacts principal digital leadership practices. A quantitative survey method was employed, collecting data from 382 university teachers in Changchun city, China, with Pearson correlation and multiple regression data analysis. The results revealed that there is a positive relationship between teacher technology adoption and principal digital leadership, as well as confirmed a statistically regression model from teacher technology adoption to principal digital leadership practice. The further analysis showed that communication dimension contributes most, while teaching dimension has a very weak effect on principal digital leadership practice. The study provides valuable contributions to both theory and practice, discusses the findings and implications in detail. The significance of the study derives from its ability to deepen our understanding of the reciprocal influence between digital leadership and technology adoption in higher education, offering insights for future research and practical applications in similar contexts.